The relationship between maximal strength and plyometric ability in rugby players - Dymond, C.; Flanagan, E. P.; Turner, A. P. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
This study examined the role of maximal strength in plyometric exercise performance in twenty strength-trained rugby players. Players' maximal leg strength was assessed using a 3 or 5RM barbell back squat strength testing procedure. Plyometric ability was assessed using ground contact times and the reactive strength index variable during depth jumps from a variety of box heights (12, 36 and 51cm) performed on a force plate. The data indicated a strong positive relationship between strength levels and plyometric ability. Stronger subjects achieved better reactive strength indices than weaker counterparts and are more capable of performing depth jumps at higher intensities. Stronger athletes may benefit more from fast SSC plyometric training than their weaker counterparts.